The effects of environmental enrichment on physiology of landlocked salmon; aspects of growth, tissue energy metabolism and stress - Wahlsten, Aliisa (My University, 2025)
Global climate change has led to an increase in environmental stressors, including the increased frequency of warming and the prevalence of pollutants in waters, which significantly impact aquatic ecosystems. Fish are particularly vulnerable to these changes which might lead to mass death of fish species. Stocking of hatchery-reared fish in nature is one way how the wild fish populations are supported. However, hatchery-reared fish that have lived their life in controlled hatchery environment before release to nature, have been found to have lower survival chances in natural environments. Environmental enrichment is known to help fish to adapt and manage stress better. This is done in controlled settings by simply adding objects and changing the water velocities in the tanks to make their hatchery environment more natural. While environmental enrichment has a huge potential for improving fish fitness, its impact on the health and metabolism of hatchery-raised landlocked salmon (Salmo salar m. sebago) facing climate-related stress is still not well understood. This study investigates the effects of environmental enrichment on the body growth, stress cortisol hormone in plasma and energy metabolism of cardiac and skeletal muscles in hatchery-reared landlocked salmon. This study supports the hypothesis that rearing landlocked salmon in a more complex environment would enhance their physiological and metabolic responses, promoting growth, stress resilience, and muscle oxygenation. The results of this study showed that environmental enrichment significantly increased mass, capillary density in red muscle and lowered cortisol levels, changes that may improve the endurance of fish and readiness for survival in natural habitats.
Keywords: Enriched environment, rearing tank, landlocked salmon, sea trout, CS, LDH, cortisol